Women’s Masonry in Madrid from 1869 to 1939 - Según-Alonso, Manuel (2019)
In Madrid during the late nineteenth-century and first third of the twentieth-century there were among the freethinking and republican circles, influenced by laicism, many women seeking the principles of freedom, equality and fraternity that Freemasonry defends. Through this work, we intend to recover the work done by women's Masonry in Madrid and its contribution to the feminist cause, the emancipation of women, and the progress of society as a whole. I aim to recover the work of all Adoption and mixed Lodges in Madrid and the name of their members.